The Relationship Of Exclusive Breastfeeding With Stunting Incidents In Toddler In Dt Village - Bangun, Sri Melda Br; Sihombing, Julita Rotua (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2024)
Stunting or short stature is a serious nutritional problem that is currently of concern to the Indonesian government because it has a negative impact on reducing the quality of human resources in the future. Indonesia is the country with the fifth largest incidence of stunting out of 88 countries in the world and the third highest after Timor Leste and Democratic Laos in the South-East Asia Regional (SEAR) region, with stunting sufferers of 7.8 million or 35. 65%. Exclusive breastfeeding is one of the factors that can influence the prevalence of stunting because the nutrition contained in breast milk is an important factor that determines a child's growth and development. The aim of this research was to determine the relationship between exclusive breastfeeding and the incidence of stunting in toddlers in Dolok Tolong Village, Sumbul District, Dairi Regency. The research design used was an analytical survey with a cross-sectional study design. The sample was 38 toddlers. The results obtained were that the majority of the samples were aged 11-20 months (21.1%), 26 toddlers who were not given exclusive breastfeeding (68.4%), and 9 toddlers (23.7%) were included in the stunting category. Based on the test results statistics using the chi square correlation test, the results showed that there was a significant relationship between exclusive breastfeeding and the incidence of stunting (p=0.002). It is hoped that the results of this research can contribute to related parties, especially Community Health Centers, regarding exclusive breastfeeding to overcome stunting